Lac Cultivation as a Risk-coping Strategy for Agriculture in Jharkhand - Pal, Govind; Bhagat, M. L.; Bhattacharya, A. (Indian Forester, 2009)
The present paper is based on the analysis of survey data of 500 lac growers of Ranchi and West Singhbhum districts in the year 2003-04 and 2004-05. Primary data has been collected from the lac growers. The analysis of survey data shows that contribution of lac in total income and farm income was 18.5% and 26.4% respectively for untrained, while 24.0% and 32.0% respectively for trained lac growers. Cost of cultivation and net return per host on Palas (Butea monosperma) worked out to Rs. 51.30 and Rs. 97.70 respectively for untrained and Rs. 70.70 and Rs.163.40 respectively for trained lac growers. Cost of cultivation and net return per host on Ber (Zizyphus mauritiana) worked out to Rs. 93.50 and Rs. 195.40 respectively for untrained and Rs. 159.20 and Rs.418.30 respectively for trained lac growers. Cost of cultivation and net return per host on Kusum (Schleichera oleosa) worked out to be Rs. 688.10 and Rs. 1,628.40 respectively for untrained and Rs. 1,104.20 and Rs. 3,312.90 respectively for trained lac growers. Due to very low investment in fixed cost, break even production was very low in comparison to existing production for both untrained and trained lac growers. Low break even prices show that risk in lac cultivation is very low and it will be a profitable enterprise even in low lac prices. Risk bearing ability was more in case of trained lac growers in comparison to untrained lac growers.